Enteric Escherichia coli O157:H7 in Cattle, and the Use of Mice as a Model to Elucidate Key Aspects of the Host-Pathogen-Microbiota Interaction: A Review - Lange, Maximo E.; Uwiera, Richard R. E.; Inglis, G. Douglas (Frontiers in Veterinary Science, 2022)
Enterohemorrhagic Escherichia coli (EHEC) serotype O157:H7 is responsible for foodborne disease outbreaks, typically associated with the consumption of undercooked foods contaminated with cattle manure containing the bacterium. At present, effective mitigations do not exist. Many of the factors regulating enteric colonization by E. coli O157:H7 in cattle, and how cattle respond to the bacterium are unknown. In this regard, intestinal colonization locations, shedding patterns, interactions with the enteric microbiota, and host immune responses to infection are current knowledge gaps. As disturbances to host homeostasis are believed to play an important role in the enteric survival of the bacterium, it is important to consider the potential importance of stress during cattle production. Husbandry logistics, cost, and the high genetic, physiological, and microbial heterogeneity in cattle has greatly hampered the ability of researchers to elucidate key aspects of the host-pathogen-microbiota interaction. Although mice have not been extensively used as a cattle model, the utilization of murine models has the potential to identify mechanisms to facilitate hypothesis formulation and efficacy testing in cattle. Murine models have been effectively used to mechanistically examine colonization of the intestine, host responses to infection, and to interactively ascertain how host physiological status (e.g., due to physiological stress) and the enteric microbiota influences colonization and disease. In addition to reviewing the relevant literature on intestinal colonization and pathogenesis, including existing knowledge gaps, the review provides information on how murine models can be used to elucidate mechanisms toward the development of rationale-based mitigations for E. coli O157:H7 in cattle.